2014
DOI: 10.1128/jcm.01010-14
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin-Induced Mutations in ileS in Various Genetic Backgrounds of Methicillin-Resistant Staphylococcus aureus

Abstract: Topical mupirocin is widely used for the decolonization of methicillin-resistant Staphylococcus aureus (MRSA) carriers. We evaluated the capacity of various MRSA clonotypes to develop mutations in the ileS gene associated with low-level mupirocin resistance. Twenty-four mupirocin-sensitive MRSA isolates from a variety of genotypes (determined by a multilocus variablenumber tandem-repeat assay) were selected. Mupirocin MICs were determined by Etest. The isolates were then incubated in subinhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…At the molecular level, low-level resistance (indicated by MICs of 8 to 256 mg/ml) is determined by point mutations in the isoleucyl-tRNA synthetase gene (ileS) (76,(83)(84)(85)(86), which is chromosomally borne (in contrast to plasmid borne). A range of point mutations have been associated with low-level resistance, with the most commonly reported mutations being V588F and V631F (74,76,87). These mutations are located in the Rossman fold, thereby limiting the ability of mupirocin to bind to the isoleucyl-tRNA synthetase enzyme (76).…”
Section: Currently Used Topical Antibacterial Agents Mupirocinmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, low-level resistance (indicated by MICs of 8 to 256 mg/ml) is determined by point mutations in the isoleucyl-tRNA synthetase gene (ileS) (76,(83)(84)(85)(86), which is chromosomally borne (in contrast to plasmid borne). A range of point mutations have been associated with low-level resistance, with the most commonly reported mutations being V588F and V631F (74,76,87). These mutations are located in the Rossman fold, thereby limiting the ability of mupirocin to bind to the isoleucyl-tRNA synthetase enzyme (76).…”
Section: Currently Used Topical Antibacterial Agents Mupirocinmentioning
confidence: 99%
“…These mutations are located in the Rossman fold, thereby limiting the ability of mupirocin to bind to the isoleucyl-tRNA synthetase enzyme (76). Importantly, the presence of these mutations has not been shown to confer a significant bacterial fitness cost in vitro, suggesting a possible fitness advantage for these low-level resistant strains in the context of ongoing mupirocin use (84,85,87). Interestingly, one recent study demonstrated the rapid development of mutations associated with low-level mupirocin resistance after only 14 days of exposure to subinhibitory mupirocin concentrations, with mutations being stably maintained in the absence of mupirocin (87).…”
Section: Currently Used Topical Antibacterial Agents Mupirocinmentioning
confidence: 99%
“…Low-level mupirocin-resistant (LL-MR) S. aureus strains are defined as exhibiting an MIC of 8 to 256 g ml Ϫ1 due to point mutations in the organism's native isoleucyl-tRNA synthetase gene (ileRS) and develop rapidly in both the laboratory and clinical settings (28). High-level mupirocin resistance (HL-MR) (MIC of Ͼ256 g ml Ϫ1 ) occurs less frequently and is attributable to the acquisition of a mobile genetic element harboring either mupA, which codes for an alternate isoleucyl-tRNA synthetase, or the less-characterized mupB gene (29,30).…”
mentioning
confidence: 99%
“…to 350 described by Lee et al [24]. The N213D mutation had been previously reported, and are considered to have no impact on the sensitivity of MUP [25].…”
Section: Mechanism Of Retapamulin Resistancementioning
confidence: 82%
“…In addition, no other mutations in IleS were found. Lee et al [24] reported that a mutation of S634F could confer phenotype of susceptibility or MuL in diverse isolates. In view of this phenomenon, the contribution of N213D mutation to MuL should be evaluated further.…”
Section: Mechanism Of Retapamulin Resistancementioning
confidence: 99%